Renal Denervation for Refractory Hypertension – Technical Aspects, Complications and Radiation Exposure - Scheurig-Muenkler, C.; Weiss, W.; Foert, E.; Toelle, M.; van der Giet, M.; Kröncke, T. J.; Zidek, W.; Powerski, M.-J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To analyze procedural details, complications and radiation exposure in renal denervation (RDN) using the Medtronic Symplicity® device in the treatment of refractory hypertension.Materials and Methods: Fifty three consecutive patients underwent RDN. The number of ablations per artery, peri-procedural complications, procedure time (PT), fluoroscopy time (FT), dose-area product (DAP) and procedure-related complications were documented. Additionally, the radiation dose was compared between obese (body mass index ≥ 30 kg/m²) and non-obese patients.Results: Bilateral RDN was performed in 50/53 (94 %) cases and with a minimum of 4 ablations per artery in 33/50 (66 %), the mean count being 5.4 (range R: 2 – 13) on the right and 4.3 (R: 1 – 10) on the left. The FT and DAP decreased significantly over the first 12 procedures, reaching a steady state with a median FT of 11.2 min (R: 7.5 – 27) and a median DAP of 4796 cGy × cm² (R: 1076 – 21 371), resulting in an effective dose of 15.7 mSv. The median PT was 57 min (R: 40 – 70). Obese patients had a 3.3-fold higher radiation dose (p < 0.001). We observed one severe spasm and one imminent respiratory depression, both resolved without sequelae.Conclusion: For an experienced interventionalist, RDN has a short learning curve with a low risk profile. The radiation dose does not exceed that of other renal artery interventions, but is explicitly higher in obese patients, who account for a large portion of patients with refractory hypertension.
Keywords: renal arteries; ablation procedures; hypertension; denervation; radiation dose